2008
DOI: 10.1021/bi800828u
|View full text |Cite
|
Sign up to set email alerts
|

Amylin Proprotein Processing Generates Progressively More Amyloidogenic Peptides that Initially Sample the Helical State

Abstract: Human amylin, or islet amyloid polypeptide, is a peptide co-secreted with insulin by the beta cells of the pancreatic islets of Langerhans. The 37-residue, C-terminally amidated human amylin peptide derives from a proprotein that undergoes disulfide bond formation in the endoplasmic reticulum and is then subjected to four enzymatic processing events in the immature secretory granule. Human amylin forms both intracellular and extracellular amyloid deposits in the pancreas of most Type II diabetic subjects, like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
166
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(191 citation statements)
references
References 50 publications
24
166
1
Order By: Relevance
“…However, this state likely does not reflect the physiologic conformation of IAPP monomers, which have been reported to have a higher α-helical content. 9,37 Following 1 h of incubation, the minimum at 201 nm decreased in intensity, a local maximum developed at 208 nm, and a minimum developed at 220 nm, suggesting formation of a mixture containing both α-helix and β-sheet structures. 38 With continued incubation, the maximum at 208 nm increased in intensity and shifted slightly toward shorter wavelengths.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…However, this state likely does not reflect the physiologic conformation of IAPP monomers, which have been reported to have a higher α-helical content. 9,37 Following 1 h of incubation, the minimum at 201 nm decreased in intensity, a local maximum developed at 208 nm, and a minimum developed at 220 nm, suggesting formation of a mixture containing both α-helix and β-sheet structures. 38 With continued incubation, the maximum at 208 nm increased in intensity and shifted slightly toward shorter wavelengths.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…Subsequent CD studies demonstrated that the hIAPP monomer adopts primarily a random coil structure. 16,[33][34][35][36][37] Recent NMR studies on human amylin, 38 rat amylin and pramlintide peptides, which have sequences similar to that of amylin, suggest that an α-helical structure is adopted near the N-terminus. 39,40 By interpreting the results of ion mobility mass spectroscopy experiments with a molecular implicit-solvent model, Dupuis et al 29 showed that the hIAPP monomer adopts an α-helical conformation between residues 9-17 on the terminus end, and a short β-hairpin between residues 24-28 and 31-35 on the C-terminus.…”
Section: Introductionmentioning
confidence: 99%
“…Brender et al, 7 for example, showed that membrane disruption and amyloid formation are two separate processes that happen in different regions of hIAPP. Liposome leakage experiments on full-length hIAPP and hIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] fragments at low concentration confirmed that the pathological membrane-disrupting activity comes from the IAPP N-terminal region as both sequences induce almost identical ABSTRACT: The loss of the insulin-producing β-cells in the pancreatic islets of Langerhans, responsible for type-II diabetes, is associated with islet amyloid deposits. The main component of these deposits is the amyloid fibrils formed by the 37-residue human islet amyloid polypeptide (hIAPP also known as amylin).…”
Section: Introductionmentioning
confidence: 99%
“…However, the peptide is exposed to the water, whereas hIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] is buried within the micelle. Interestingly, protonation of His18 of hIAPP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] drives the peptide to the surface of the membrane and decreases its toxicity. 29,30 To better understand the role of the disulfide bridge and the amino acid sequence on the early stage of aggregation in solution, we study the full-length hIAPP dimer, with and without the disulfide bridge, and compare its conformational properties with that of the monomer, already studied by us, 20 as well as with rIAPP in both monomeric and dimeric forms.…”
Section: Introductionmentioning
confidence: 99%